Clash: Amazon versus Walmart - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 2024)
Amazon and Walmart, with more than half a trillion in revenues annually, are the two largest companies in the world. They have not only redefined the retail industry-- Walmart in the 1980s/1990s and Amazon since 2000-- but have also been the benchmark for business best practices (e.g., the use of IT, supply chain, data analytics, customer orientation). This year, it is anticipated that Amazon will dethrone Walmart as the world's largest company, a position that Walmart has occupied for more than two decades. By examining these two companies and their business models in depth, the author elucidates on the more general phenomenon of incumbents competing with disruptors (e.g., Volkswagen vs Tesla, Marriott vs Airbnb) as well as the move to omnichannel retail where physical stores must coexist with online retailers.